African Americansà pursuit of self-employment - Magnus Lofstrom; Timothy Bates (Institute for the Study of Labor (IZA), 2007)
This study examines causes of black/white gaps in business ownership and self-employment rates by analyzing small-business entry and exit patterns. We proceed by recognizing heterogeneity in business ownership across different industry groups: a classification of firms by human- and financial-capital intensiveness, or entry barriers, we find, is useful for explaining racial differences in entrepreneurship. The barriers facing aspiring entrepreneurs seeking entry into low-barrier industries differ substantially from those limiting entry into high-barrier industries. Higher entry and lower exit rates typifying whites, relative to African Americans, are traditionally interpreted as reflections of the greater financial- and human-capital resources possessed by non-minorities. This consensus view, however, is simplistic. While education background is a powerful predictor of self-employment patterns in the low-barrier industries, advanced educational credentials actually predict lower entry: college graduates are less likely to select into low-barrier small business ownership. In the high-barrier fields, in contrast, college-educated individuals are more likely than less educated persons to enter into self employment. Overall, black presence in high-barrier fields is held down by lower net asset holdings and weaker educational credentials of potential and actual entrepreneurs. In the low-barrier industries, where the majority of black-owned businesses operate, net worth levels and educational backgrounds are trumped by the racial characteristic: low black entry and high exit rates are powerfully predicted by one's race.
Keywords: J15; 330; Self-employment; entrepreneurship; entry barriers; African American; Selbstständige; Unternehmer; Farbige Bevölkerung; Bildungsniveau; USA